# Solve for Y 10y-2(-4+3y)=(66-21y)/-3 10y-2(-4+3y)=66-21y-3
Simplify the left side.
Simplify each term.
Apply the distributive property.
10y-2⋅-4-2(3y)=66-21y-3
Multiply -2 by -4.
10y+8-2(3y)=66-21y-3
Multiply 3 by -2.
10y+8-6y=66-21y-3
10y+8-6y=66-21y-3
Subtract 6y from 10y.
4y+8=66-21y-3
4y+8=66-21y-3
Simplify 66-21y-3.
Cancel the common factor of 66-21y and -3.
Factor 3 out of 66.
4y+8=3(22)-21y-3
Factor 3 out of -21y.
4y+8=3(22)+3(-7y)-3
Factor 3 out of 3(22)+3(-7y).
4y+8=3(22-7y)-3
Move the negative one from the denominator of 22-7y-1.
4y+8=-1⋅(22-7y)
4y+8=-1⋅(22-7y)
Rewrite -1⋅(22-7y) as -(22-7y).
4y+8=-(22-7y)
Apply the distributive property.
4y+8=-1⋅22-(-7y)
Multiply.
Multiply -1 by 22.
4y+8=-22-(-7y)
Multiply -7 by -1.
4y+8=-22+7y
4y+8=-22+7y
4y+8=-22+7y
Move all terms containing y to the left side of the equation.
Subtract 7y from both sides of the equation.
4y+8-7y=-22
Subtract 7y from 4y.
-3y+8=-22
-3y+8=-22
Move all terms not containing y to the right side of the equation.
Subtract 8 from both sides of the equation.
-3y=-22-8
Subtract 8 from -22.
-3y=-30
-3y=-30
Divide each term by -3 and simplify.
Divide each term in -3y=-30 by -3.
-3y-3=-30-3
Cancel the common factor of -3.
Cancel the common factor.
-3y-3=-30-3
Divide y by 1.
y=-30-3
y=-30-3
Divide -30 by -3.
y=10
y=10
Solve for Y 10y-2(-4+3y)=(66-21y)/-3

### Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top